Clusterin ameliorates diabetic atherosclerosis by suppressing macrophage pyroptosis and activation - Xuan, Lingling; Ren, Lulu; Kang, Xiaoxu; Chang, Rui; Zhang, Wen; Gong, Lili; Liu, Lihong (Frontiers in Pharmacology, 2025)
BackgroundIt has been demonstrated that clusterin (CLU) is a protective protein involved in a variety of diseases and disorders. However, the role of CLU in diabetic atherosclerosis is not elucidative. The objective of this study is to investigate the role of CLU in diabetic atherosclerosis and the molecular mechanisms.MethodIn in vivo experiments, Clu knockout and overexpressed murine models were used to investigate the role of Clu in diabetic atherosclerosis. Atherosclerotic plaque formation was determined by hematoxylin-eosin (H&E) staining and Oil Red O staining. F4/80 and CD68 levels were determined by immunohistochemical staining. Transmission electron microscopy was used to observe changes in cell pyroptosis morphology. NLRP3 and IL-1β levels were determined by Western blot and immunofluorescence staining. In in vitro experiments, TNF-α, IL-6, and IL-1β levels in THP-1 derived macrophages were determined by real-time qPCR and ELISA.ResultsWe found that Clu-overexpression reduced while Clu knockout promoted atherosclerotic plaque formation, macrophage infiltration and inflammatory factor expression in mouse aortic plaques. Consistently, CLU overexpression inhibits the production of TNF-α, IL-6, and IL-1β in THP-1 derived macrophages. Moreover, Clu inhibited the release of inflammatory factors and macrophage pyroptosis in diabetic atherosclerosis murine models.ConclusionOur study revealed that CLU could ameliorate diabetic atherosclerosis via suppressing inflammatory factors release and pyroptosis of macrophage. CLU may be a promising therapeutic target for diabetic atherosclerosis.